2021
DOI: 10.1039/d1ra05877k
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable diastereomeric effect on thermoresponsive behavior of polyurethane based on lysine and tartrate ester derivatives

Abstract: The long-distance diastereomeric effect on thermoresponsive properties in a polyurethane system consisting of chiral monomers was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…However, the reported HMDI-based PUs bearing up to three-unit OEG (OEG 3 ) chains as side chains do not have enough hydrophilicity to overcome the HMDI hydrophobicity, which challenged its dissolution in water to later form CNF-based nanocomposites. We have previously demonstrated that hexamethylene (HDI) or l -lysine ethyl ester diisocyanate (LDI)-based PUs required two OEG 3 chains as hydrophilic moiety for making PUs soluble in water, which exhibited lower critical solution temperature behavior around 30–40 °C. , Thus, we selected PEG1000 as the hydrophilic moiety to ensure sufficient hydrophilicity for dispersity in water and designed a water-soluble comb and linear PUs consisting of HMDI and PEG1000. Figure a,b shows the chemical structure of comb PU and linear PU, named PU-G and PU-L, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reported HMDI-based PUs bearing up to three-unit OEG (OEG 3 ) chains as side chains do not have enough hydrophilicity to overcome the HMDI hydrophobicity, which challenged its dissolution in water to later form CNF-based nanocomposites. We have previously demonstrated that hexamethylene (HDI) or l -lysine ethyl ester diisocyanate (LDI)-based PUs required two OEG 3 chains as hydrophilic moiety for making PUs soluble in water, which exhibited lower critical solution temperature behavior around 30–40 °C. , Thus, we selected PEG1000 as the hydrophilic moiety to ensure sufficient hydrophilicity for dispersity in water and designed a water-soluble comb and linear PUs consisting of HMDI and PEG1000. Figure a,b shows the chemical structure of comb PU and linear PU, named PU-G and PU-L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among branched polymers, comb and bottlebrush polymers have well-defined structures consisting of a backbone with side chains and can be defined through topological parameters. Recently, quantified topological structures of comb and bottlebrush polymers have been associated with a sigmoid-shaped mechanical and rheological behavior, mimicking soft biological tissues through the dilution of entanglement by the steric repulsion of side chains. , Thus, comb and bottlebrush polymers are an ideal class of branched polymers with unique rheological properties, in addition to low T g and hydrophilicity, and can be expected to behave differently from previous CNF nanocomposites with linear topological isomers. In this context, our reported comb polyurethanes (PUs) bearing poly­(ethylene glycol) (PEG) side chains are a good model for understanding the topological effects of soft-phase polymers in the CNF nanocomposite because of their easy tailoring of the comb topology, water solubility, mechanical and rheological properties, and the promising high molecular cohesion of the urethane bonds. …”
Section: Introductionmentioning
confidence: 99%